Gas Wars: crony capitalism and the Ambanis - "Thakurta, Paranjoy Guha; Ghosh, Subir; Chaudhuri, Jyotirmoy " (Delhi, 2014)
The two brothers had fought over many issues, but what sometimes got lost in the din of the battle cries was a simple fact: much of the tussle was over India's natural resources, about how the resources were intended to be mined, marketed and monetised.' Paranjoy Guha Thakurta shows how the simmering controversy over the rich natural gas reserves in the Krishna-Godavari Basin boiled over into a primetime storm on gas pricing involving the office of the Comptroller and Auditor General of India, the Ministry of Petroleum and Natural Gas as well as the Prime Minister's Office, even as he introduces new dimensions to it. While many reasons have been attributed to the split in the powerful Indian business family, the Ambanis, this book argues that the battle between the Ambani brothers was largely about wresting control over reserves of natural gas that are below the ocean bed along the basin of the two greatest rivers of southern India. With painstaking research, a meticulous perusal of press reports, as well as a few surprising exclusives, Gas Wars highlights cases of crony capitalism that allowed the Reliance group to blatantly exploit loopholes which were consciously retained in the system to benefit it. Even as the book tells the story of how the country's largest corporate conglomerate has benefited from the way government policies are structured, it lays bare the alarming facts of a natural disaster waiting to happen due to the ruthless exploitation of the country's natural resources in order to swell the fortunes of a few.
Keywords: Ambani family